Development and Application of Quadruple Luminex xTAG Method for Simultaneous Detection of Japanese Encephalitis Virus, West Nile Virus, Yellow Fever Virus and Zika Virus - Junying SUN; Qiwen WU; Jichu LI; Chunhong LI; Pengju GUO; Yi HUANG; Feifei YIN (Guangdong nongye kexue)
【Objective】The zoonotic infectious diseases caused by arbovirus of family Flavivirus have a severe impact on China's animal husbandry and public health. Due to the wide types and similar infection symptoms of arbovirus, as well as its heavy clinical surveillance, the study aims to establish a fast and high-throughput detection technology for four serious Flavivirus arbovirus to provide technical support for clinical diagnosis and epidemiological monitoring of arbovirus.【Method】Based on Luminex xTAG technology, four pairs of specific primers were designed for 5' UTR of Japanese encephalitis virus (JEV), 5' UTR and part of C gene of West Nile virus (WNV), 5' UTR of yellow fever virus (YFV), NS5 gene of Zika virus (ZIKV), and were modified with TAG sequence and Biotin. Multiplex PCR amplification was carried out with standard virus strains as model. Then, PCR products were hybridized with magnetic beads with complementary TAG sequences and streptavidin-phycoerythrin, and the fluorescence signals of magnetic beads and phycoerythrin were detected by Luminex 200 instrument to indicate the classification and quantification of the pathogens of the arbovirus samples.【Result】The Luminex xTAG method applied to detect JEV, WNV, YFV and ZIKV was established, and the optimal primer working concentration was 0.5, 0.5, 0.75, 0.5 µmol/L; the established hybridization system and reaction conditions were: 20 μL of magnetic bead working solution, 5 μL of PCR amplification product, and 75 μL of SAPE working buffer solution; the hybridization temperature, hybridization time and pH value were 37 ℃, 30 min, and 8.0, respectively. The quadruple Luminex xTAG method could detect JEV, WNV, YFV and ZIKV simultaneously, and there was no cross reaction with dengue virus. The duplicate test results indicated that, the coefficient of variation of the intra-assay for quadruple Luminex xTAG method was 2.50%-5.63% and inter-assay was 3.61%-12.50%. The detection limits of JEV and ZIKV were 1×104 copies/μL, and those of WNV and YFV were 1×103 copies/μL, respectively. The sensitivity for WNV, YFV and ZIKV was 10 to 100 times that of conventional PCR. A total of 209 clinical samples and simulated samples were detected by Luminex xTAG and RT-qPCR methods, with the coincidence rate of JEV, MNV, YFV and ZIKV of 100%.【Conclusion】The established quadruple Luminex xTAG method has high throughput, high specificity and sensitivity as well as high cost-effectiveness, providing a high-throughput technology method for clinical diagnosis and epidemiological monitoring of arboviruses.